1997
DOI: 10.1007/bf02744478
|View full text |Cite
|
Sign up to set email alerts
|

Jet flames from noncircular burners

Abstract: Gas jets from noncircular exits entrain more air from surroundings than jets from circular exits of equivalent area. Because the mixing rate of fuel and air governs the combustion and pollutant emission of diffusion flames and partially premixed flames, noncircular geometries offer a passive control of the flame characteristics. In this paper, the literature on nonburning, noncircular jets is reviewed and recent studies on noncircular jet flames are discussed with focus on the work conducted in the author's la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Different bandsof OH [(2, 0), (1, 0), (3,2), and (0, 0)] are detected in the emission spectra. It is observed that the OH radical formation is higher in the elliptic co ow ames than in the circular co ow ame.…”
Section: Radiation Spectral Measurementsmentioning
confidence: 99%
“…Different bandsof OH [(2, 0), (1, 0), (3,2), and (0, 0)] are detected in the emission spectra. It is observed that the OH radical formation is higher in the elliptic co ow ames than in the circular co ow ame.…”
Section: Radiation Spectral Measurementsmentioning
confidence: 99%
“…The effects of burner shape and orientation of elliptic burner on flame characteristics were analyzed. The most previous research set the fuel orifice as a circle or ellipse, and the flame characteristic is different between those two burners’ shapes. Papanikolaou et al suggested the fuel exit shape holds an important effect on flame characteristics including flame size and radiation. Akbarzadeh and Birouk conducted experiments to study the effect of fuel nozzle orifice geometry including circular and rectangular on liftoff of coflowing nonpremixed turbulent methane flame.…”
Section: Introductionmentioning
confidence: 99%
“…Gutmark and Grinstein 17 highlighted the favorable impact of flow ellipticity on the turbulence development and combustion performance by indicating the vortical flow pattern associated with the axis switching. The elliptical jets reduce the soot and NOx emissions from partially premixed flames, 18 while increasing the aspect ratio (defined as the major to the minor diameter ratio) enhances the flow stretch and provides more increase in the combustion efficiency of nonpremixed flames. 19 These features are favorably coupled to the strain rate corresponding to the jets' mutual impingement in both flame modes.…”
Section: Introductionmentioning
confidence: 99%